Decontamination of Chlorella sp. Culture using antibiotics and antifungal cocktail treatment - Mustapa, Mokhzanni; Sallehudin, Nor Jannah; Mohamed, Mohd Shamzi; Mohammad Noor, Normawaty; Ahmad Raus, Raha (Asian Research Publishing Network, 2016)
Direct sampling of microalgae from nature inevitably brings together the problem of massive growth of bacteria and fungi. In this study, bacterial and fungal contamination level was evaluated from the Chlorella sp. isolated from two different locations of local freshwater area. Attempts to obtain axenic Chlorella sp. culture by combinations of antibiotic and antifungal at different range of concentration treatment were investigated. It is evident that there were three different bacteria and two different fungi present in the culture, but apparently sterility can be achieved when ampicillin, cefotaxime and carbendazim cocktail were employed at concentrations of 700 µg/mL, 200 µg/mL and 0.1µg/mL, respectively. These concentrations are also proven harmless toward Chlorella sp. as higher concentrations inhibit the growth of microalgae. It was found that by streaking the contaminated microalgae twice onto the TAP agar containing the previously described cocktail, completely removed the contaminating fungi and bacteria from the culture. In conclusion, this study suggested that axenic Chlorella sp. can be attained with this method and cocktail recipe.